2016
DOI: 10.1037/a0039961
|View full text |Cite
|
Sign up to set email alerts
|

The influence of family-supportive supervisor training on employee job performance and attitudes: An organizational work–family intervention.

Abstract: Training supervisors to increase their family-supportive supervisor behaviors (FSSB) has demonstrated significant benefits for employee physical health, job satisfaction, and turnover intentions among employees with high levels of family-to-work conflict in prior research in a grocery store context. We replicate and extend these results in a health care setting with additional important employee outcomes (i.e., employee engagement, organizational commitment, and supervisor ratings of job performance), and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(90 citation statements)
references
References 58 publications
(119 reference statements)
4
82
0
4
Order By: Relevance
“…Two interventions had positive effects on well-being (subjective indicators and the broader class of indicators; Biggs, Brough, and Barbour 2014;Odle-Dusseau et al 2016) and all three had some beneficial effects on job design. Of the two studies that examined performance, one indicated a positive effect (Odle-Dusseau et al 2016) and one indicated no effect (Biggs, Brough, and Barbour 2014).…”
Section: Interventions Focused On Training Leaders To Improve Job Desmentioning
confidence: 99%
See 1 more Smart Citation
“…Two interventions had positive effects on well-being (subjective indicators and the broader class of indicators; Biggs, Brough, and Barbour 2014;Odle-Dusseau et al 2016) and all three had some beneficial effects on job design. Of the two studies that examined performance, one indicated a positive effect (Odle-Dusseau et al 2016) and one indicated no effect (Biggs, Brough, and Barbour 2014).…”
Section: Interventions Focused On Training Leaders To Improve Job Desmentioning
confidence: 99%
“…(2) Interventions focused on training leaders to improve job design for those they manage (Biggs, Brough, and Barbour 2014;Elo et al 2014;Odle-Dusseau et al 2016). These interventions were considered to be related to changes in job design and other employment practices because training was used to improve job design.…”
Section: Papers Included In Systematic Reviewmentioning
confidence: 99%
“…First, the positive correlations of service-member reported FSSB with key job attitudes (JS, OC) is consistent with previous literature (Odle-Dusseau et al, 2016). However, this study extends this line of research to this unique sample (service-members in civilian workplaces) which has important implications for workplaces seeking to become employers of choice for service-members returning to the civilian workplace.…”
Section: Discussionsupporting
confidence: 78%
“…Importantly, they also found that even employees without dependents at home felt benefitted from family-supportive workplace policies as measured by engagement and subjective well-being (Matthews et al, 2014). Even more recent research shows substantive relationships between improvements in employee perceptions of FSSB following a supervisor intervention and employee reports of job satisfaction and organizational commitment (Odle-Dusseau, Hammer, Crain, & Bodner, 2016 Hypothesis 1. Service member reported FSSB will be positively related to a) job satisfaction, b) affective organizational commitment, c) work-to-family enrichment and d) negatively related to work-to-family conflict.…”
Section: Family-supportive Supervisor Behaviors the First Decade Of mentioning
confidence: 99%
“…Employees who work in family supportive environments are likely to have a lower desire to leave the organization (Odle-Dusseau, Hammer, Crain, & Bodner, 2016), thus attenuating the potential costs associated with turnover. Research reveals that turnover intentions predict actual turnover (Batt & Valcour, 2003;Behson, 2005;Maertz, Griffeth, Campbell, & Allen, 2007).…”
Section: Introductionmentioning
confidence: 99%